A new revolutionary paradigm of software development for mainstream business operations. (1st January 2000) - Park, June S.
This paper discusses software engineering methods to create and maintain operations support systems (OSSs) that can enhance the global competitiveness of businesses. In particular, two related methods - model-based development (MBD) and component-based development (CBD) methods - are discussed. CBD is widely regarded as revolutionising the software industry. The purpose of this paper is to improve correct understanding of the advantages of MBD and CBD over traditional methods when they are applied to developing mainstream business applications. We introduce a market-leading, computer-aided software engineering (CASE) tool to illustrate the concepts underlying MBD and CBD.